I Feel Different, but in Every Case I Feel Proud: Distinguishing Self-Pride, Group-Pride, and Vicarious-Pride - De Hooge, Ilona E.; Van Osch, Yvette (Frontiers in Psychology, 2021)
Various lines of research have hinted at the existence of multiple forms of the self-conscious emotion pride. Yet, thus far it is unclear whether forms such as self-pride, group-pride, or vicarious-pride are characterized by a similar feeling of pride, and what the communal and unique aspects are of their subjective experiences. The current research addresses this issue and examines the communal and unique characteristics of the subjective experiences of self-pride, group-pride, and vicarious-pride. Using recalled experiences, two experiments demonstrate that self-pride, group-pride, and vicarious-pride can be separated on the basis of their subjective experiences. More specifically, Experiment 2 demonstrates how self-pride, group-pride, and vicarious-pride are related to feelings of self-inflation, other-distancing versus approaching, and other-devaluation versus valuation. Finally, Experiment 3 shows that especially responsibility for the achievement, but also the number of people having contributed to the achievement, influence the experience of other-oriented forms of pride. The current findings reveal that self-pride, group-pride, and vicarious-pride are all forms of pride with distinct subjective experiences. These findings provide valuable insights into the emotion pride, and may lead to divergent consequences for sociality, self-consciousness, and behavior.